Green synthesis of selenium nanoparticles using aloe leaf extract and evaluation of acute toxicity of materials - Le Minh Tri; Vu, Tri Thien (Journal of Military Science and Technology, 2024)
The element selenium (Se) is of great importance in many fields, such as physics, chemistry, and biology. Selenium is also an important trace element, which has a great influence on biological systems due to its antioxidant, anticancer and antiviral activities. Selenium deficiency can lead to a number of serious diseases such as cancer, cardiovascular disease, immune disorders, or cause immunosuppression. Selenium nanoparticles are much more biologically active than other forms of selenium that exist in the form of inorganic salts or in organic compounds. In this paper, selenium nanoparticles are synthesized using a green method using aloe vera leaf extract which acts as a reducing agent and dispersion stabilizer. The properties of the post-synthetic materials analyzed by UV-vis spectroscopy, selected area diffraction (SAED), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS) showed that the synthesized selenium nanoparticles were in the range of 30 - 70 nm. The results of the assessment of acute toxicity in rats showed a lethal concentration (50% death of mice) of 10,374 mg/kg.